Joshua F. Speed correspondence - Speed, Joshua F. (Joshua Fry), 1814-1882.
ALS (1840 December 24 and 25) from Speed to his mother, Lucy Gilmer Fry Speed, pertaining to personal matters.
Kentucky state legislator, farmer, real estate investor, and close friend of Abraham Lincoln from Speed's years in Springfield, Illinois.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Speed, Lucy Gilmer Fry, -- 1788-1874 -- Correspondence; Farmers; Legislators -- Kentucky; Real estate investors